Hyperbaric storage at room temperature with several short intermittent interruption periods at atmospheric pressure results in similar microbial growth inhibition and inactivation as without interruption - Duarte, Ricardo V. (2022)
In order to study the possible effect of several compressions and decompressions (C/D) cycles performed during hyperbaric storage (HS) in microbial behaviour, raw milk was stored under 75 MPa at room temperature (RT) for 31 days, under three different total C/D cycles conditions, 5, 31 and 93. The different C/D cycles achieved similar microbiological counts reduction for the same sampling period, independently of the number of C/D cycles, with Dp-values around 3.5 and 19 days for Enterobacteriaceae and total aerobic mesophiles, respectively, reaching similar microbial levels at the end of the storage period. These results contribute to enhance HS research, allowing the use of a single vessel with several samples to be taken along time, since several C/D cycles have no effect on results, thus leading to faster research advances in the field of HS.